Kelimpahan Pakan Rusa (Cervus timorensis) di Taman Wisata Alam dan Cagar Alam Pangandaran - Asep Purwanto (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2013)
The research on abudance and species diversity of birt with the IPA (Indices Ponctuels d’Abondence). method was used to sample the birds in the Ciremai mount area, and also dird identification guide book for determine. A total of 60 individual birds belonging to 23 families and 46 species was recorded. The dominant family was silsiidae, comprising 8 species (13,33%) of the total species. The most abundant species in the mount Ciremai was the burung kacamata biasa (Zosterops palpebrosus). The analysis of abudance and species diversity of bird status was achieved about 11 endemic species, and 15 species as restricted range bird. Based on Indonesia Governmen Policy and IUCN International Convention, there are 21 species as the protected bird. There were 15 feeding guild group of bird include 48 species as insectivore, 8 species as carnivore and 4 species as herbivore. The factors with threat to bird population and its habitat are : 1). Illegal hunting, 2). Forest destruction and 3). Forest fire